Evaluation of the moisture management, air and water vapour permeabilities of knitted fabrics for garments / Nurul Sarah Aliah Mat Adini ... [et al.] - Mat Adini, Nurul Sarah Aliah; Ahmad, Mohd Rozi; Nor Affandi, Nor Dalila; Aminuddin, Mohammad Muhaimin (Research Management Institute (RMI), 2023)
The market today offers a variety of fabrics that may be utilised to create any style of clothing. Fabrics are periodically altered as a result of technology's continual growth, to the point that it became difficult for clothes makers to assess the fabric characteristics related to thermal comfort. This paper reports some investigations on the moisture management and permeability properties of several commercial knitted fabrics intended for garment application. The fabric's ability to manage moisture as well as its air and water vapour permeability were assessed. A fabric rating index was used to combine the results from each test to determine the fabric's thermal comfort characteristics. Among the five knitted fabrics, the fabric comprised of nylon & polyester with jersey structure gave the highest assessment rating which is 5. The study serves as a future reference for future textile and garment industry, that implement the laboratory method used in this paper i.e moisture management, water vapour and air permeability in choosing the better thermal comfort qualities for general wear.